Skeletal muscle contributions to reduced fitness in cystic fibrosis youth - Tomlinson, Owen William; Barker, Alan Robert; Fulford, Jonathan; Wilson, Paul; Shelley, James; Oades, Patrick John; Williams, Craig Anthony (Frontiers in Pediatrics, 2023)
Background: Increased maximal oxygen uptake (V̇O2max) is beneficial in children with cystic fibrosis (CF) but remains lower compared to healthy peers. Intrinsic metabolic deficiencies within skeletal muscle (muscle ‘quality’) and skeletal muscle size (muscle ‘quantity’) are both proposed as potential causes for the lower V̇O2max, although exact mechanisms remain unknown. This study utilises gold-standard methodologies to control for the residual effects of muscle size from V̇O2max to address this ‘quality’ versus ‘quantity’ debate. Methods: Fourteen children (7 CF vs. 7 age- and sex-matched controls) were recruited. Parameters of muscle size – muscle cross-sectional area (mCSA) and thigh muscle volume (TMV) were derived from magnetic resonance imaging, and V̇O2max obtained via cardiopulmonary exercise testing. Allometric scaling removed residual effects of muscle size, and independent samples t-tests and effect sizes (ES) identified differences between groups in V̇O2max, once mCSA and TMV were controlled for. Results: V̇O2max was shown to be lower in the CF group, relative to controls, with large ES being identified when allometrically scaled to mCSA (ES = 1.76) and TMV (ES = 0.92). Reduced peak work rate was also identified in the CF group when allometrically controlled for mCSA (ES = 1.18) and TMV (ES = 0.45). Conclusions: A lower V̇O2max was still observed in children with CF after allometrically scaling for muscle size, suggesting reduced muscle ‘quality’ in CF (as muscle ‘quantity’ is fully controlled for). This observation likely reflects intrinsic metabolic defects within CF skeletal muscle.